2022
DOI: 10.1038/s41598-022-09980-6
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 and SARM1 modulate survival and chemoresistance in an HPV-positive cervical cancer cell line

Abstract: Human Papillomavirus is responsible for a wide range of mucosal lesions and tumors. The immune system participate in tumorigenesis in different ways. For example, signaling pathways triggered by Toll-like receptors (TLR) play a role in chemotherapy resistance in several tumor types and are candidates for contributing to the development of HPV-induced tumors. Here, we studied the receptor TLR4 and the adaptor molecule SARM1 in HeLa cells, an HPV-positive cervical cancer cell line. Knocking out of these genes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…SARM1 gene has been linked to prostate cancer [41]. Moreover, SARM1 has been suggested to be valuable for therapy resistance and could be a relevant clinical target for cervical cancer [42]. Also, this gene has been documented to be patent for Colorectal cancer [43].…”
Section: Resultsmentioning
confidence: 99%
“…SARM1 gene has been linked to prostate cancer [41]. Moreover, SARM1 has been suggested to be valuable for therapy resistance and could be a relevant clinical target for cervical cancer [42]. Also, this gene has been documented to be patent for Colorectal cancer [43].…”
Section: Resultsmentioning
confidence: 99%
“…According to recent ndings, viral infection causes the gene expression of TLR4 to be highly expressed in positive samples, the high level of TLR4 gene expression has an obvious association with tumors resulting from the transformation of squamous cells of the cervix into immortal cells by the carcinogenic proteins of the HPV (12), when compared with negative samples of cervix tissue , which compatible with studies by (13), its found that TLRs, particularly TLR4, TLR5, and TLR9, are very associated with HPV infection, and cervical cancer cells may grow faster if TLR4 is activated. Studies investigated, the connection between TLR4 and cervical cancer cells in vitro (13), and discovered that TLR4 supported HPV-related cervical cancer cells in proliferating and resisting apoptosis (14), this shows that the high level of TLR4 gene expression in positive cases was connected with HPV infection. where the level of TLR4 gene expression was lower in negative than the positive samples, Additionally, when the TLR4/MyD88/NF-B pathway is activated, proin ammatory cytokines are abundantly produced in HPV-related cervical cancer cells (15).…”
Section: Discussionmentioning
confidence: 98%
“…Very little has been reported regarding its role in cancer. One study with HeLa cells, an HPV-positive cervical cancer cell line, found that knocking out SARM1 decreased cell survival and increased the cells' sensitivity to cisplatin treatment [127].…”
Section: Sarm1mentioning
confidence: 99%